Efeitos não-adiabáticos na espectroscopia de alta resolução de moléculas primordiais - Paulo Henrique Ribeiro Amaral (2019)
The elaboration of a physical model that correctly describes the dynamics of the processof vibration and rotation of the molecules is essential to obtain their energy levels withgreat accuracy. During rovibrational motion, the atomic nuclei that make up the moleculemove around the equilibrium position. On the basis of this fact, it is common to thinkthat all electrons also participate in vibrations and molecular rotations. However, duringrovibrational processes only part of the electronic cloud follows the nuclear movement.For example, considering a covalently bonded diatomic molecule, it is expected that thenumber of electrons moving with nuclei near equilibrium geometry will be less than whenatoms are far apart. In the equilibrium region, part of the electrons is involved in thebonding and does not move with the nuclei whereas in the dissociation region all electronsfollow the vibrational and rotational motion of the nuclei. Thus, it is concluded that lumpscomposed of atomic nuclei and fractions of electrons that depend on molecular coordinatesmove subject to an effective electrostatic potential. Assuming this and incorporating thischaracteristic into the molecular equations that provide the rovibrational energies, it ispossible to obtain results that strongly agree with highly accurate experimental data.Accurate calculation of rovibrational energy levels depends on obtaining a highly accurateBorn-Oppenheimer potential energy curve (CEP) – or surface – and including adiabatic,relativistic, and quantum electrodynamic effects. QED). Even so, the deviations fromthe experiments are around cm−1. The reason for this is the absence of non-adiabaticeffects that are related to coupling of electronic states, which directly affect the energies.Using core masses whose values depend on molecular geometry, it is possible to take intoaccount the non-adiabatic effects that are commonly overlooked due to the great difficultythey impose on calculations, even for simple molecules like H2. However, the electronicmasses that make up the core masses must be correctly determined or, in turn, lead towrong results. One way to obtain the correct value of these core electron fractions is toanalyze the densities of the AIM (atoms im molecules) and, from the attractive potentialsof atomic nuclei, to define the value of these masses, a methodology proposed by thepresent work. With this method, curves and reduced mass surfaces dependent on molecularcoordinates were determined, which made it possible, together with curves and surfacesof high accuracy potentials - without QED - to calculate of complete linelists of highlyaccurate rovibrational transitions of light molecules important for astronomy, especially instudies of the early universe such as HD+, HD, He+and isotopologists, H+3and D+3.